2004
DOI: 10.1210/jc.2003-031982
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Behavior and Outcome of Papillary Thyroid Cancers Smaller than 1.5 cm in Diameter: Study of 299 Cases

Abstract: To investigate predictors of relapse in small ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
210
7
11

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(260 citation statements)
references
References 20 publications
32
210
7
11
Order By: Relevance
“…The datasets used in the present study lack information regarding recurrence. However, other longitudinal institutional studies have shown no difference in recurrence rates between T1a and T1b tumors at five years (10,11), and up to 15 years following the time of diagnosis (16)(17)(18).…”
Section: T1a Versus T1b Differentiated Thyroid Cancersdiscussionmentioning
confidence: 91%
“…The datasets used in the present study lack information regarding recurrence. However, other longitudinal institutional studies have shown no difference in recurrence rates between T1a and T1b tumors at five years (10,11), and up to 15 years following the time of diagnosis (16)(17)(18).…”
Section: T1a Versus T1b Differentiated Thyroid Cancersdiscussionmentioning
confidence: 91%
“…Moreover, some authors have insisted that there was no statistically significant difference between papillary microcarcinomas and papillary thyroid carcinomas at clinical follow-up. 11,24 Thus, establishing the predictive factors that differentiate between silent and potentially aggressive papillary microcarcinomas would be of great value. S100A4 is a member of the S100 family of calcium-binding proteins, also known as metastasin, fibroblast-specific protein, pEL-98, 18A2, CAPL or calvasculin.…”
Section: Discussionmentioning
confidence: 99%
“…8 Although its clinical significance in papillary microcarcinomas is somewhat controversial, several authors have reported that lymph node metastasis at presentation is correlated with loco-regional recurrence in papillary microcarcinomas. 5,[9][10][11] Moreover, lymph node metastasis is reported to be associated with distant metastasis of papillary microcarcinomas. [9][10][11] In the new TNM (tumor, node, metastases) staging system, lymph node metastasis is a more important factor than tumor size in overall staging.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Others, however, have concluded that, in low-risk patients, the incremental benefit of remnant ablation is unclear (22). Patients with papillary microcarcinoma receive ablation, especially when multicentricity, lymph node metastases and vascular or capsular invasion are encountered (23).…”
Section: Postoperative Radioiodine Administrationmentioning
confidence: 99%